2019
DOI: 10.1371/journal.pone.0216499
|View full text |Cite
|
Sign up to set email alerts
|

Fractionating auditory priors: A neural dissociation between active and passive experience of musical sounds

Abstract: Learning, attention and action play a crucial role in determining how stimulus predictions are formed, stored, and updated. Years-long experience with the specific repertoires of sounds of one or more musical styles is what characterizes professional musicians. Here we contrasted active experience with sounds, namely long-lasting motor practice, theoretical study and engaged listening to the acoustic features characterizing a musical style of choice in professional musicians with mainly passive experience of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 59 publications
3
13
0
5
Order By: Relevance
“…Consistent with former findings about experience-dependent plasticity in musicians, we found enhanced auditory ERPs in musicians compared to non-musicians, with greater magnitude of both MMN components (Herholz and Zatorre, 2012;Kraus and Chandrasekaran, 2010;Lappe et al, 2008;Shahin et al, 2003;Vuust et al, 2011Vuust et al, , 2012bVuust et al, , 2012a. Nonetheless, since the main focus of the study was on the role played by BDNF in neuroplastic changes induced by training, and since the differences between musicians and non-musicians have been widely described by former studies (Brattico et al, 2001;Kliuchko et al, 2019b;Schlaug, 2015;Steele et al, 2013;Vuust et al, 2005;Vuust et al, 2012b) we did not focus on this detail. Instead, we mainly focused on the differences between musicians in relation to their genotype.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Consistent with former findings about experience-dependent plasticity in musicians, we found enhanced auditory ERPs in musicians compared to non-musicians, with greater magnitude of both MMN components (Herholz and Zatorre, 2012;Kraus and Chandrasekaran, 2010;Lappe et al, 2008;Shahin et al, 2003;Vuust et al, 2011Vuust et al, , 2012bVuust et al, , 2012a. Nonetheless, since the main focus of the study was on the role played by BDNF in neuroplastic changes induced by training, and since the differences between musicians and non-musicians have been widely described by former studies (Brattico et al, 2001;Kliuchko et al, 2019b;Schlaug, 2015;Steele et al, 2013;Vuust et al, 2005;Vuust et al, 2012b) we did not focus on this detail. Instead, we mainly focused on the differences between musicians in relation to their genotype.…”
Section: Discussionsupporting
confidence: 87%
“…In accordance with our hypothesis, we observed an effect of the Val66Met polymorphism on were generally modest in size, between-group differences were consistently found within 100-200ms from the onset of the deviant stimulus, with the sole exception of rhythm, for which the difference was greatest around 300ms. Nonetheless, previous studies using the same paradigm as the one used here (Bonetti et al, 2017;Kliuchko et al, 2019b) reported a later MMN component for the rhythm deviant compared to the other musical features. Thus, it is plausible to assume that the observed modulatory effect of the polymorphism affected a subset of the physiological processes involved in MMN generation.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Crucially, deviants are more easily detected and the amplitude of the MMN becomes larger, when melodies are predictable and when the listener is a musician (Quiroga-Martinez et al, 2019a). Yet, despite the growing empirical evidence (Garrido et al, 2013; Hsu et al, 2015; Kliuchko et al, 2019; Southwell & Chait, 2018; Tervaniemi et al, 2014), little is known about the fluctuations in effective connectivity and neuronal dynamics that mediate these phenomena.…”
Section: Introductionmentioning
confidence: 99%